1995
DOI: 10.1016/0014-5793(95)00586-x
|View full text |Cite
|
Sign up to set email alerts
|

An interface point‐mutation variant of triosephosphate isomerase is compactly folded and monomeric at low protein concentrations

Abstract: Wild-type trypanosomal triosephosphate isomerase (wtTIM) is a very tight dimer. The interface residue His-47 of wtTlM has been mutated into an asparagine. Ultracentrifagation data show that this variant (H47N) only dimerises at protein concentrations above 3 mg/ml. H47N has been characterised at a protein concentration where it is predominantly a monomer. Circular dichroism measurements in the near-UV and far-UV show that this monomer is a compactly folded protein with secondary structure similar as in wtTIM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…[41][42][43][44][45] These attempts to monomerize TIM involved deletions in the interfacial loop 3 and mutations that reversed charge pairing. We hypothesized that by choosing the most common amino acid at each position of cTIM, we had scrambled necessary amino acid interactions (i.e., correlations) at the dimer interface.…”
Section: Engineering the Interface Of Ctimmentioning
confidence: 99%
See 1 more Smart Citation
“…[41][42][43][44][45] These attempts to monomerize TIM involved deletions in the interfacial loop 3 and mutations that reversed charge pairing. We hypothesized that by choosing the most common amino acid at each position of cTIM, we had scrambled necessary amino acid interactions (i.e., correlations) at the dimer interface.…”
Section: Engineering the Interface Of Ctimmentioning
confidence: 99%
“…The structure of TIM suggests that dimerization is necessary for full assembly of the active site by the interdigitation of loop 3 from the opposite monomer, and engineered monomeric TIMs exhibit k cat /K m values reduced by about 10 4 -fold. [41][42][43][44][45] The quaternary structure of cTIM was determined by gel-filtration chromatography (Fig. 1c).…”
Section: Consensus Timmentioning
confidence: 99%
“…Several studies on triosephosphate isomerases from various sources showed that different mutations in the dimer interface lead to monomers with different levels of activity. Some of these mutants showed concentration-dependent specific activity, suggesting that the inactive monomers can associate, at least to some degree, to give an active dimer (4,19,27,34).…”
mentioning
confidence: 99%
“…By using such an approach, it has been shown that mutations of different enzymes resulted in either active or inactive monomers (1,24,26). One of the most studied enzymes in this regard is triosephosphate isomerase, which usually forms a stable and tightly bound dimer (4). Several studies on triosephosphate isomerases from various sources showed that different mutations in the dimer interface lead to monomers with different levels of activity.…”
mentioning
confidence: 99%
“…That is, in the intermediate state, the compact domain of the chain has substantially less structural fluctuations than the non-compact portion. Goldberg, 1980Banik et al, 1992Herold & Kirschner, 1990Mei et al, 1992Aceto et al, 1992Akasaka et al, 1982Shaw et al, 1995Borchert et al, 1995 "The 3-state dimers. The table describes the PDB code with the chain names, name of the molecule, the resolution of the structure, number of amino acids in a single chain, and the reference which shows the dimerization is 3-state.…”
Section: Dimer Kineticsmentioning
confidence: 99%